2017
DOI: 10.1038/tp.2017.154
|View full text |Cite
|
Sign up to set email alerts
|

RNA-seq analysis of amygdala tissue reveals characteristic expression profiles in schizophrenia

Abstract: The amygdala brain region has been implicated in the pathophysiology of schizophrenia through emotion processing. However, transcriptome messages in the amygdala of schizophrenia patients have not been well studied. We used RNA sequencing to investigate gene-expression profiling in the amygdala tissues, and identified 569 upregulated and 192 downregulated genes from 22 schizophrenia patients and 24 non-psychiatric controls. Gene functional enrichment analysis demonstrated that the downregulated genes were enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 53 publications
5
29
0
Order By: Relevance
“…Using a shRNA‐mediated knock‐out of SERPING1 to silence the gene expression, a recent study suggests knock‐out of this gene impairs neuronal migration and affects brain development . Preliminary evidence in a study of complement genes in twins with SZ implicated peripheral expression of C5 and SERPING1 to be associated with cortical thinning in the superior frontal region; SERPING1 has also been found to be overexpressed in the amygdala of patients with SZ . In animal studies, C1 inhibitor created by SERPING1 attenuated acute neurobehavioral deficits, ischemic volume, and neurodegeneration .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a shRNA‐mediated knock‐out of SERPING1 to silence the gene expression, a recent study suggests knock‐out of this gene impairs neuronal migration and affects brain development . Preliminary evidence in a study of complement genes in twins with SZ implicated peripheral expression of C5 and SERPING1 to be associated with cortical thinning in the superior frontal region; SERPING1 has also been found to be overexpressed in the amygdala of patients with SZ . In animal studies, C1 inhibitor created by SERPING1 attenuated acute neurobehavioral deficits, ischemic volume, and neurodegeneration .…”
Section: Discussionmentioning
confidence: 99%
“…40 Preliminary evidence in a study of complement genes in twins with SZ implicated peripheral expression of C5 and SERPING1 to be associated with cortical thinning in the superior frontal region 4 ; SERPING1 has also been found to be overexpressed in the amygdala of patients with SZ. 42 In animal studies, C1 inhibitor created by SERPING1 attenuated acute neurobehavioral deficits, ischemic volume, and neurodegeneration. 43 Therefore, SER-PING1 is a gene pivotal to inflammatory response regulation, neural development, and a key contributor to complement cascade activation.…”
Section: Enrichment Analysis Of Complement Genesmentioning
confidence: 99%
“…In particular, synaptoporin, which is exclusively enriched in granule cell axons, is a synaptic vesicle marker for hippocampal mossy fibers ( Romer et al, 2011 ). Patients with schizophrenia have both decreased synaptoporin levels ( Guillozet-Bongaarts et al, 2014 ; Chang et al, 2017 ) and mossy fiber deficits ( Kolomeets et al, 2007 ), indicating that synaptoporin expression may be a good marker for hippocampal synaptic disturbances in schizophrenia. In the presents study, we demonstrated synaptoporin deficit in MIA offspring, even in the absence of gross anatomical alterations in the brain or neuronal loss.…”
Section: Discussionmentioning
confidence: 99%
“…At last, a total of 16 modules were detected across the four tissues as shown in Table 3. The functional terms enriched in the 16 modules were detected with the Database for Annotation, Visualization and Integrated Discovery (DAVID, version 6.8) [52], where only the most enriched term was shown for each module in Table 3 where pathways associated with ribosome and immune response were also enriched [57,58]. Another, the functional component of lipid droplet in Small Bowel (p=5.8110 -8 , module 1) is a main organelle that has important roles in regulating lipid metabolism [59].…”
Section: The Network Modules Uncover Biological Processes Implicated mentioning
confidence: 99%